Propriety of Dewey Decimal Classification (DDC) Scheme in Classifying Buddhist Literature: an analytical view with Reference to ‘Tripitaka' - Gallaba, G.M.P.; Samaradiwakara, G.D.M.N.; Samaravickrama, P.G.R. (Proceedings of International Conference of University Librarians' Association of Sri Lanka (ICULA) 2016, 2016)
Attached
Keywords: Dewey Decimal Classification (DDC); Tripitaka; Buddhist Literature; Library Classification